Pilot scheduling algorithm based on cell classification-cross entropy for massive MIMO - Yinhui YU; Heng ZHOU; Ying YANG; Hao PAN; Jiapeng REN (Tongxin xuebao)
The massive MIMO system is equipped with a large number of antennas at the base station to serve many users, but it is affected by the inter-cell interference which called pilot contamination. A pilot scheduling scheme was designed to reduce the effect of pilot contamination. Pilot scheduling problem belongs to the arrangement optimization problem, and the algorithm computational complexity of greedy algorithm to search the optimal solution is greatly. In order to reduce the influence of the interference of the community, a new pilot scheduling schemes was proposed by so this article using cell classification and cross entropy(CE) mechanism to reduce the effect of pilot contamination on the system. The simulation results show that the proposed algorithm can not only improve the performance of the system, but also reduce the computational complexity.